THE TRANSFORMATION OF PERSUASIVE TECHNIQUES IN POLITICAL COMMUNICATION IN THE DIGITAL ERA - Ahmad Sampurna Rambe; Gita Vita Loka; Muhammad Darul Fikhry; Fahira Rahmah Hani; Aprilian Valentiyo (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study explores persuasive techniques in political communication in the ever-evolving digital era, where social media platforms offer real-time interaction opportunities while simultaneously presenting significant challenges. The research focuses on the importance of a deep understanding of complex audience characteristics, the spread of disinformation, and the urgent need for ethical and socially responsible dimensions in every political campaign. Using a qualitative approach with literature review and content analysis methods, this article identifies various persuasive strategies, including compelling narratives, emotional appeal, message repetition, and the integration of accurate data and facts to build credibility. The findings reveal that the effectiveness of persuasion depends not only on communication skills but also on the communicator's ability to adapt to audience skepticism, understand cultural contexts, and counter hoaxes. Therefore, this study concludes that a holistic and sustainable approach combining persuasive expertise with integrity, transparency, and a commitment to democratic dialogue is key to achieving political goals and fostering meaningful public participation.